“We Cure Sickle Cell Disease with Herbs”: Perspectives of Herbal Medicine Practitioners Treating Sickle Cell Disease in the Acholi Sub-Region - Awor S; Opee J; Ocaya D; Ocaya J; Abola B; Malinga GM; Oryema C; Arwenyo B; Ongwech A; Musoke D; Nnamuyomba P; Epila J (Journal of Multidisciplinary Healthcare)
Silvia Awor,1– 3 Jimmyy Opee,1,3 Denis Ocaya,4 Jimmy Ocaya,5 Benard Abola,6 Geoffrey Maxwell Malinga,2 Christine Oryema,2 Beatrice Arwenyo,5 Acaye Ongwech,5 David Musoke,7 Proscovia Nnamuyomba,5 Jackie Epila8 1Department of Obstetrics and Gynaecology, Faculty of Medicine, Gulu University, Gulu, Uganda; 2Department of Biology, Faculty of Science, Gulu University, Gulu, Uganda; 3Department of Women’s and Children’s Health, University of Liverpool, Liverpool, UK; 4Department of Pathology, Faculty of Medicine, Gulu University, Gulu, Uganda; 5Department of Chemistry, Faculty of Science, Gulu University, Gulu, Uganda; 6Department of Mathematics, Faculty of Science, Gulu University, Gulu, Uganda; 7Department of Pharmacology and Therapeutics, Faculty of Medicine, Gulu University, Gulu, Uganda; 8Department of Chemistry, Faculty of Education, Lira University, Lira, UgandaCorrespondence: Silvia Awor, Email s.awor@gu.ac.ugBackground: Sickle cell disease (SCD) is a genetic blood disorder that results in the deformation of red blood cells under low oxygen conditions, causing vaso-occlusive crises and severe complications. While hydroxyurea has been introduced as a treatment for SCD, herbal medicines remain widely used across Africa. Northern Uganda has a high SCD prevalence of 20.5%, yet limited research exists on alternative treatment options within local communities. This study aimed to explore the perspectives of herbal medicine practitioners in the Acholi sub-region.Methods: We conducted in-depth interviews between October and December 2024 involving 24 herbal medicine practitioners in the Acholi sub-region, selected through referrals and non-probability snowball sampling. All data collected were recorded, transcribed verbatim, and analyzed using thematic content analysis, and emerging themes were presented.Results: All participants believed herbal medicine could cure SCD, and the majority reported successfully treating patients. However, some practitioners remembered some patients who reported being sick with sickle cell crises many years after the “cure”. “When they report improvement, I stop medication after some time…” thereafter, “I encourage them to go to the hospital, but they do not. They can stay without falling sick for a long time and declare themselves healed”. Findings suggest herbal medicines are commonly used for SCD management in the Acholi sub-region. Most herbal medicine practitioners rely on the hospital diagnoses, although a few can tell who has sickle cell disease by looking at or touching them. A lot of mistrust exists between herbal medicine practitioners, the government, and researchers. This hinders efforts to integrate traditional medicine into mainstream healthcare and limits opportunities for scientific validation.Conclusion: Herbal medicine practitioners believe herbs can treat sickle cell disease; however, further research is needed to investigate the nature of these herbs and their mechanisms of action, thereby facilitating the integration of herbal medicine into conventional care. We discuss some implications of the study for practice and policy.Keywords: sickle cell disease, herbal medicine, alternative treatment, traditional medicine, Northern Uganda, Africa